Flood Disaster in Semarang City from Colonial to Reformasi: A Review of its Management - Kurniawan, Edi; Suharini, Erni (Paramita: Historical Studies Journal, 2021)
This article reveals Semarang City’s history, an extremely vulnerable area to floods and examines what the government has done to overcome this greatly chronic problem. Its default condition as a lowland city in direct contact with hilly areas and sea makes the potential for floods exhaustive. Thus, it is prone to pluvial, local, and coastal floods. Various policies carried out from the colonial era to the Semarang City government have so far not been able to control floods as expected. Countermeasures using non-structural methods through spatial planning and environmental law enforcement have yielded no specific results. Countermeasures with structural methods such as river normalization or the construction of flood control infrastructure become no more than a dull blade. For years, spatial planning policies have been implemented and many infrastructures have been built, but the threat of flooding is increasing and expanding. It is necessary to change the development paradigm adopted by the government so that it no longer boosts infrastructure and investment, then re-applies the memayu hayuning bawana philosophy.Artikel ini mengungkap sejarah Kota Semarang yang sangat rentan terhadap banjir dan mengkaji apa yang telah dilakukan pemerintah untuk mengatasi masalah yang sangat kronis ini. Kondisi bawaannya sebagai kota dataran rendah yang bersentuhan langsung dengan daerah perbukitan dan laut membuat potensi banjir sangat besar. Sehingga rawan terhadap banjir pluvial, lokal, dan pesisir. Berbagai kebijakan yang dilakukan sejak zaman penjajahan hingga pemerintah Kota Semarang selama ini belum mampu mengendalikan banjir seperti yang diharapkan. Penanggulangan dengan metode non-struktural melalui penataan ruang dan penegakan hukum lingkungan belum membuahkan hasil yang spesifik. Penanggulangan dengan metode struktural seperti normalisasi sungai atau pembangunan infrastruktur pengendalian banjir tidak lebih dari pisau tumpul. Selama bertahun-tahun, kebijakan penataan ruang telah diterapkan dan banyak infrastruktur telah dibangun, tetapi ancaman banjir semakin meningkat dan meluas. Perlu mengubah paradigma pembangunan yang dianut pemerintah agar tidak lagi menggenjot infrastruktur dan investasi, kemudian kembali menerapkan filosofi memayu hayuning bawana.